2011
DOI: 10.1242/dmm.007831
|View full text |Cite
|
Sign up to set email alerts
|

A high level of liver-specific expression of oncogenic KrasV12 drives robust liver tumorigenesis in transgenic zebrafish

Abstract: SUMMARYHuman liver cancer is one of the deadliest cancers worldwide, with hepatocellular carcinoma (HCC) being the most common type. Aberrant Ras signaling has been implicated in the development and progression of human HCC, but a complete understanding of the molecular mechanisms of this protein in hepatocarcinogenesis remains elusive. In this study, a stable in vivo liver cancer model using transgenic zebrafish was generated to elucidate Ras-driven tumorigenesis in HCC. Using the liver-specific fabp10 (fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 52 publications
6
90
2
Order By: Relevance
“…E-cadherin, a binding partner of β-catenin, also plays critical roles in liver tumorigenesis as a suppressor of tumor and invasion20. Our previous study has shown the gradual activation of WNT/β-catenin pathway through nuclear localization of β-catenin and loss of E-cadherin during kras -induced liver tumorigenesis21. In normal livers, β-catenin was localized in the cell membrane.…”
Section: Resultsmentioning
confidence: 98%
“…E-cadherin, a binding partner of β-catenin, also plays critical roles in liver tumorigenesis as a suppressor of tumor and invasion20. Our previous study has shown the gradual activation of WNT/β-catenin pathway through nuclear localization of β-catenin and loss of E-cadherin during kras -induced liver tumorigenesis21. In normal livers, β-catenin was localized in the cell membrane.…”
Section: Resultsmentioning
confidence: 98%
“…This was subjected to semiquantitative RT-PCR with previously published primers for TCR-b chains (Vb1.5/17.5, Vb12) and Ig heavy chains (igVH1, igVH4) (46,47). Total RNA was also subjected to quantitative RT-PCR (QRT-PCR) with the following primers: il-2rgc.a 59-GTCACTGGTCTTGTATGCTGT and 59-GCTCTCACTATCACTGCTGG, il-2rgc.b 59-AGAAAGACCCAAGCCA-GT and 59-ATCTTTTTCCTCTCACAGTACC, jak3 59-AACAGAGC-GAGCAGCAGAGAG and 59-GTGTGACCACCCTTCCTTCC, pik3cg 59-AGGGGCACTTGTGATTGAG and 59-CTTCACTATTTCAATCATTC-CAA, b-actin 59-TGGCATCACACCTTCTAC and 59-AGACCATCACCA-GAGTCC and map2k1 and map2k2 (48). Data were normalized to b-actin, and fold change was calculated using the DDCt method.…”
Section: Rt-pcr Quantitative Rt-pcr and 59racementioning
confidence: 99%
“…Numerous studies in zebrafish have shown that constitutive or inducible transgenic expression of oncogenic forms of the Ras/mitogen-activated protein kinase signaling cascade, often activated in human HCC, can induce zebrafish liver tumors. Expression of k-ras (V12), human Δ RAF1, and constitutively active xmrk (zebrafish homolog of epidermal growth factor receptor) lead to the development of HCC that is treatable with MEK/ERK and PI3K/AKT inhibitors (71, 108, 129, 130). Comparative gene expression studies have shown that human and zebrafish HCCs have generally conserved expression profiles, including similar markers of tumor progression (71, 99, 100, 129).…”
Section: Modeling Human Liver Disease Mechanisms In Zebrafishmentioning
confidence: 99%